Adaptação, desenvolvimento e evidências de validade e precisão de instrumentos de avaliação dos componentes de leitura no ensino fundamental II - Brito, Gabriel Rodriguez (2017)
Reading is characterized as a complex activity. International prevalence studies indicate that students with difficulties in reading and writing match up to 17.5% of the Elementary School students, which have lower performance according to the level expected in their education. Different models have tried to explain the cognitive processes involved in the reading ability. According to the Componential Model, the reading performance involves several factors, divided into three domains: cognitive, psychological and ecological. Regarding the cognitive domain, reading with comprehension can be understood as the product of the interaction of decoding processes, comprehension and fluency. Studies have shown that the identification of possible difficulties of these abilities can provide appropriate intervention, resulting in significant improvement in the ability and therefore better performance in reading in general. Because of the lack of validated instruments for the reading evaluation in Brazil, this study was divided into three phases in order to, based on the cognitive neuropsychology, adapt and develop assessment tools for reading components focusing on the final years of elementary school. Three instruments were built and adapted on phase one: Teste de Compreensão de Palavras e Pseudopalavras II (TCLPP-II), which aims to investigate word recognition processes; Teste de Fluência de Leitura (TFL), in order to evaluate the fluency in reading single words and in texts; Teste Cloze de Compreensão de Leitura (TCCL) which aims evaluate reading comprehension in narrative and argumentative texts. On phase 2, a pilot study was made with 48 students from a State public school, 29 of them were from the 6th grade and 19 from the 9th grade. Preliminary analyzes of the study oriented modifications and corrections in the three instruments and demonstrated their applicability. In phase 3 an analysis of variance revealed that there was a significant improvement in performance with school progress in most of the measures in the three tests, a statistically significant difference between the 6th and the other grades. Overall, the measures of all tests correlated significantly with each other, with the other tests and with school performance, varying the magnitude of the correlations. As precision analyzes indicate adequate internal consistency of all instruments, especially for the initial grades of Elementary School II. Therefore, this research suggests that all three tests have an adequate psychometric effect.